Location and transport effects of high occupancy vehicle and bus lanes in Madrid - Miguel Mateos; Paul Pfaffenbichler (European Regional Science Association (ERSA), 2005)
Sustainability is one of today's major challenges. A widely accepted definition of sustainability is based on intergenerational equity and a set of sub objectives. Numerous studies provide evidence that cities worldwide do not fulfil the requirements of sustainability. The work presented here investigates whether transport policies of the municipality of Madrid contribute to the high level objective of sustainability. The "Comunidad de Madrid” is situated in the heart of Spain. It covers an area of 8,000 km2. About 5 million people live within the whole region. The city of Madrid itself has about 2.9 million inhabitants. The situation is characterised by a rapid development of housing and businesses in the surroundings of the city. Traffic is characterised by a high share of people commuting into the core city. Although Madrid has an efficient metro line system, this results in a high level of peak hour congestion. As well the land use as the transport system do not fulfil the requirements of sustainability. Different measures were realised and proposed to remedy the current situation. One of these measures is a bus and high occupancy vehicle (HOV) lane. The HOV lane covers a 16 kilometres long stretch of the highway N-VI and was opened in the year 1995. The strategic, dynamic land use and transport interaction model MARS (Metropolitan Activity Relocation Simulator) will be used to assess the effects of the HOV lane. MARS covers the whole "Comunidad de Madrid”. Effects on land use and regional travel patterns are predicted with this model. Observed data are used to validate the model results. The potential of the application of HOV lanes to other radial highways is assed by using a modified cost benefit analysis.
Keywords: 330